High Calcium Boba from Egg Shells to Prevent Stunting and Boost the Immune System - Laillatul Mas’udah; Dhani Wijaya; Nabila Asha Rahmita; Ulva Nur Rahmawati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Nutritional status and stunting are problems in several countries, including Indonesia. Calcium is one of the important micronutrients to prevent stunting, and the immune system can act as a second messenger of lymphocytes to maintain the body's immune response. Calcium in eggshells can be processed into boba which is popular in the community. This study aims to examine eggshells as a high-calcium food source to prevent stunting and help increase immunity. This research is a Literature Review of open access articles published in 2016 - 2021 on Google Scholar, PubMed, and Science Direct. Duplicate reports were excluded from the study. The keywords used in searching the journal in the database are eggshells, calcium, stunting, immune system, and popular foods. Research shows that every gram of eggshell contains 381 mg of calcium. Adequate calcium intake supports increasing height, maintaining bone health, and preventing stunting. Increased intracellular calcium is essential for the steps of intracellular signaling that induce proliferation, cytokine production, and regulation of several transcription factors. Eggshells can be safely consumed if they are kept for 20 minutes and finely ground with the high calcium content. High calcium boba from eggshell flour can prevent stunting and boost the immune system.